p p and q q are prime numbers so that:

p 3 q 5 = ( p + q ) 2 {p}^{3}-{q}^{5}={(p + q)}^{2} .

Find p + q p + q .

The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Finn Hulse
Apr 26, 2014

I seriously got it my first time. I plugged in p = 7 p=7 and q = 3 q=3 . In fact... wait a second. I posted this problem here . Great minds think alike! I came up with it in the back of math class. :O

Ramiel To-ong
Dec 8, 2015

nice problem

0 pending reports


Problem Loading...

Note Loading...

Set Loading...